Black Carbon (BC) mass concentrations monitoring at North Atlantic Marine Boundary Layer (MBL) - Barata, Filipe (2012)
Proceedings of the 6th International Symposium on Advanced Environmental Monitoring, Heidelberg, 26-30 June, Germany.